The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Data fusion of electronic senses and near-infrared spectroscopy for accurate authentication and quality evaluation of Hippophae species - Chunqiao Shi; Jie Yang; Yue Liu; Yaning Lin; Yi Zhang; Ce Tang (Food Chemistry, 2026)

NIR-II photoacoustic/Raman multimodal imaging for early detection of arteriovenous fistula fibrosis - Xiaobei Cai; Xinyi Liang; Youyi Zhang; Yaning Qin; Taoxia Wang; Xiaoli Liu; Yuanyuan Qiu; Huan Liu; Lin Jin; Zeyu Xiao; Kai Cui; Guiying Li (Chemical Engineering Journal, 2026)

Plastic-mediated alterations in soil microbial networks and their role in sulfamethazine degradation - Yuqiu Ye; Luoqin Shen; Da Lin; Tianlun Zhang; Yaning Wang; Lu Lu; Yifei Qin; Dong Zhu (Journal of Environmental Sciences, 2026)

Beyond static structure: high-throughput chemical cartography of dynamic cell wall assembly - Yaning Cui; Xi Zhang; Shuizhong Wang; Weiqian Wu; Jinxing Lin (Trends in Plant Science, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

The impact of the interaction between trace chloramphenicol, biofilm, and corrosion products on disinfection by-products and microbial risks in chlorinated drinking water distribution systems - Xinkai Liu; Yanliang Lin; Kaifeng Shen; Youyi Chen; Pojun Zhang; Zihui Chen; Yaning Zhang; Jing Huang; Leixuan Fu; Sibo Liu; Chun Hu; Xueci Xing; et al. (Journal of Water Process Engineering, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Sankey diagram mapping of greenhouse gas emissions in road infrastructure projects: A cradle-to-laid perspective - Yaning Qiao; Lin Zhu; Haili Cao; Zhijun Liu; Gaoxin Wang; Fanran Meng (Sustainable Cities and Society, 2025)

Effects of multispecies management on the soil protist community in Pinus massoniana plantations in subtropical China - Jiawen Jiang; Luhong Zhou; Debao Lin; Yaning Gu; Linfang Wu; Ji-Zheng He (Pedobiologia, 2025)

Microplastics-biofilm interactions in biofilm-based wastewater treatment processes: A review - Yaning Huang; Tanqiu Hu; Bincheng Lin; Youqing Ke; Jibin Li; Jinxing Ma (Environmental Pollution, 2024)

Characteristic changes in compound drought and heatwave events under climate change - Chuan Wang; Zhi Li; Yaning Chen; Lin Ouyang; Hongyu Zhao; Jianyu Zhu; Jiayou Wang; Yazhou Zhao (Atmospheric Research, 2024)

Single-cell characterization of major components of plant cell walls in situ by Raman spectroscopy - Yujian Li; Weiwei Shen; Xi Zhang; Yaning Cui; Yuanyuan Zhao; Yayu Guo; Xiaojuan Li; Shuizhong Wang; Guoyong Song; Pu Wang; Jianfeng Ma; Jinxing Lin (Science China Life Sciences, 2024)

Recent advances in biofilm technologies for breeding wastewater treatment: Fundamentals, performance and impacts of antibiotics - Bincheng Lin; Yangyu Lai; Youqing Ke; Yaning Huang; Yewen Tao; Xiaomeng Han; Jinxing Ma (Journal of Water Process Engineering, 2024)

Bubbleless membrane aeration for Chlorella vulgaris cultivation in urine at high CO2 supply - Yewen Tao; Yangyu Lai; Jieqin Zhou; Yaning Huang; Bincheng Lin; Xiaojie Mei; Zhong Zhang; Junjian Zheng; Jinxing Ma (Journal of Water Process Engineering, 2024)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

Remarkably efficient Pt/CeO2–Al2O3 catalyst for catalytic hydrodeiodination of monoiodoacetic acid: Synergistic effect of Al2O3 and CeO2 - Minghui Li; Wen Li; Yaning Yang; Dailiang Yu; Jingling Lin; Rui Wan; Hongjie Zhu (Chemosphere, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Chitin synthase is involved in vegetative growth, asexual reproduction and pathogenesis of Phytophthora capsici and Phytophthora sojae - Wei Cheng; Menglan Lin; Min Qiu; Liang Kong; Yuanpeng Xu; Yaning Li; Yan Wang; Wenwu Ye; Suomeng Dong; Shuilin He; Yuanchao Wang (Environmental Microbiology, 2019)
Summary Chitin is a structural and functional component of the fungal cell wall and also serves as a pathogen‐associated molecular pattern (PAMP) that triggers the innate immune responses of host plants. However, no or very little chitin is found in the fungus‐like oomycetes. In Phytophthora spp., the presence of chitin has not been demonstrated so far, although putative chitin synthase (CHS) genes, which encode the enzymes that synthesize chitin, are present in their genomes. Here, we revealed that chitin is present in the zoospores and released sporangia of Phytophthora , and this is most consistent with the transcriptional pattern of PcCHS in Phytophthora capsici and PsCHS1 in Phytophthora sojae . Disruption of the CHS genes indicated that PcCHS and PsCHS1 , but not PsCHS2 (which exhibited very weak transcription), have similar functions involved in mycelial growth, sporangial production, zoospore release and the pathogenesis of P. capsici and P. sojae . We also suggest that chitin in the zoospores of P. capsici can act as a PAMP that is recognized by the chitin receptors AtLYK5 or AtCERK1 of Arabidopsis . These results provide new insights into the biological significance of chitin and CHSs in Phytophthora and help with the identification of potential targets for disease control.

Loss of terrestrial water storage in the Tianshan mountains from 2003 to 2015 - Haijun Deng; Yaning Chen; Qihu Li; Guangfa Lin (International Journal of Remote Sensing, 2019)

Techniques for detecting protein-protein interactions in living cells: principles, limitations, and recent progress - Yaning Cui; Xi Zhang; Meng Yu; Yingfang Zhu; Jingjing Xing; Jinxing Lin (Science China Life Sciences, 2019)